2020
DOI: 10.1038/s41467-020-19262-2
|View full text |Cite
|
Sign up to set email alerts
|

Observation of site-controlled localized charged excitons in CrI3/WSe2 heterostructures

Abstract: Isolated spins are the focus of intense scientific exploration due to their potential role as qubits for quantum information science. Optical access to single spins, demonstrated in III-V semiconducting quantum dots, has fueled research aimed at realizing quantum networks. More recently, quantum emitters in atomically thin materials such as tungsten diselenide have been demonstrated to host optically addressable single spins by means of electrostatic doping the localized excitons. Electrostatic doping is not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
1
21
0
2
Order By: Relevance
“…The blue shift of PL of IXs in WSe 2 /MoSe 2 heterobilayers has also been reported by reducing the gap between the two layers to enhance interlayer coupling, similar to our scenario [29]. It is assumed that monolayer WSe 2 exhibits a tent-like shape around the pillar, as reported in several studies [17,32,37]. Consequently, the gap between WSe 2 and (iso-BA) 2 PbI 4 is shortened on top of the pillar, yielding enhanced interlayer coupling.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The blue shift of PL of IXs in WSe 2 /MoSe 2 heterobilayers has also been reported by reducing the gap between the two layers to enhance interlayer coupling, similar to our scenario [29]. It is assumed that monolayer WSe 2 exhibits a tent-like shape around the pillar, as reported in several studies [17,32,37]. Consequently, the gap between WSe 2 and (iso-BA) 2 PbI 4 is shortened on top of the pillar, yielding enhanced interlayer coupling.…”
Section: Resultssupporting
confidence: 89%
“…The formation of moiré potential in vdW heterostructures will change the dynamics and transport properties of IXs significantly [14,15]. Alternative to TMD vdW heterostructures, TMDs can also be combined with other layered materials to achieve interlayer coupling [16][17][18][19]. Recently, it has been demonstrated that robust IXs could be observed in TMD/ two-dimensional (2D) perovskite heterojunctions with various material combinations [20].…”
Section: Introductionmentioning
confidence: 99%
“… (C) Spin-logic with nonvolatile magnetic memory ( Khokhriakov et al., 2021 ). (D) Excitions on WSe 2 in heterostructure with a 2D magnet ( Mukherjee et al., 2020 ). Copyright 2020, Springer Nature.…”
Section: Applicationsmentioning
confidence: 99%
“… (D) Excitions on WSe 2 in heterostructure with a 2D magnet ( Mukherjee et al., 2020 ). Copyright 2020, Springer Nature.…”
Section: Applicationsmentioning
confidence: 99%
“…[ 112,183 ] What is more, with the decrease of dimensionality, the dielectric screening effect is reduced dramatically and Coulomb interactions are significantly improved, which increase the binding energy of many‐body complexes and enable stable existence at room temperature, [ 184,185 ] offering a platform to study the excitons. [ 115,186–190 ] In brief, benefitting from the excellent properties, 2D materials are intriguing for next‐generation photonic and optoelectronic devices. In this section, recent progress of intercalation applied to tune the optical and optoelectronic properties is discussed.…”
Section: Applications Of Intercalation In 2d Materialsmentioning
confidence: 99%